2018
DOI: 10.5539/elt.v11n5p39
|View full text |Cite
|
Sign up to set email alerts
|

Students and Teachers’ Causal Attributions to Course Failure and Repetition in an ELT Undergraduate Program

Abstract: This article is the product of a diagnostic research study conducted by two professors from the APRENAP research group at Universidad Surcolombiana from Neiva, Huila, Colombia. The study aimed at looking into the causes for the English courses repetition phenomenon which was evident among many students especially in the advanced semesters at the ELT undergraduate program in the university. The main purpose of this qualitative study that followed the Grounded Theory principles was to determine to which factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The results of different studies support the gaps between the theoretical tenets and the real assessment practices carried out in the learning process. Rojas and Artunduaga (2018) found out that, according to English teachers and students' perceptions, learners didn´t achieve the expected level in advanced courses, because neither the classwork nor the tests were challenging enough during the basic English classes. In addition, Arias and Maturana (2005) concluded that, even though in some school settings English teachers are trying to follow the educational policies and theoretical guidelines on evaluation, assessment and testing issues, much research should be done in our context.…”
mentioning
confidence: 99%
“…The results of different studies support the gaps between the theoretical tenets and the real assessment practices carried out in the learning process. Rojas and Artunduaga (2018) found out that, according to English teachers and students' perceptions, learners didn´t achieve the expected level in advanced courses, because neither the classwork nor the tests were challenging enough during the basic English classes. In addition, Arias and Maturana (2005) concluded that, even though in some school settings English teachers are trying to follow the educational policies and theoretical guidelines on evaluation, assessment and testing issues, much research should be done in our context.…”
mentioning
confidence: 99%